AN ANALYSIS OF ARTIFICIAL INTELLIGENCE TECHNIQUES ON ANIMATION IN ANIMATED MOVIE SERIES - Ayyappan, P; Nirmala, T (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In recent years, the animation industry has witnessed a significant transformation driven by advancements in artificial intelligence (AI) technologies. This research article explores the application of AI techniques in animation through a case study of the Ice Age movie series. Through a comprehensive analysis, we explore how AI-driven tools have impacted character animation, facial expressions, background creation, storyboard development, rendering, and audience engagement in the Ice Age franchise. By dissecting the specific AI-driven tools and methodologies employed across the movies, this analysis elucidates how AI has elevated animation quality, streamlined production processes, and fostered unprecedented levels of creativity. By examining the specific AI techniques utilized in the production of these films and their impact on animation quality and efficiency, this study sheds light on the evolving relationship between technology and creative expression in animated filmmaking, landscape of animation production and its implications for storytelling and visual aesthetics.